Growth and Yield of Shallot (Allium cepa L. Aggregatum group) with Application of Beneficial Microorganisms - Taufiq Hidayat; Prapto Yudono; Endang Sulistyaningsih; Arif Wibowo (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2018)
Shallot (Allium cepa L. Aggregatum group) is one of the most widely utilized vegetables by Indonesian people. Some technologies have been adapted to improved shallot productivity. One of those are the application of beneficial microorganisms. We applied mycorrhizal fungi, Trichoderma sp., and Bacillus thuringiensis as well as the combination among these microorganisms were applied in Shallots cultivation and were investigated to improve the growth and development of shallot. A field experiment was arranged in a Randomized Complete Block Design with two treatment factors. The first factor consisted of two shallot cultivars, namely Biru Lancor and Crok Kuning; whilst the second factor consisted of six beneficial microorganism treatments, i.e. control, mycorrhizae, Trichoderma sp., Bacillus thuringiensis, the combination of mycorrhizae and Trichoderma sp., and the combination of those three microorganisms. The observation was conducted on infection percentage of mycorrhizae, total population of Trichoderma sp., leaf area, leaf area index, net assimilation rate, crop growth rate, harvest index, and plant yield. The data obtained were subjected to analysis of variance (ANOVA) and continued with Duncan’s Multiple Range Test (DMRT) at 5% significance level. The results showed the leaf area of shallot was improved as affected by the application of mycorrhizal fungi. The effectiveness and implication of mycorrhizal fungi on shallot growth would decrease if the application of was combined with other microorganisms. However, the application of beneficial microorganisms had not been able to increase component yield and yield of Biru Lancor and Crok Kuning, indicated by bulb weight, number of bulb, bulb diameter, number of bulb per cluster, and bulb yield per hectare.